The Influence of Green Marketing on Purchase Intention for BYD Electric Cars - Aryaputra Pratama, Mohammad Dimas; Kusuma Wardhani, Nuruni Ika (Universitas Muhammadiyah Pontianak, 2025)
This study uses a quantitative approach to examine how consumers' purchase intentions toward BYD electric automobiles are impacted by green marketing. Green products, green pricing, green distribution, and green promotion are the four aspects that are used to analyze green marketing. 102 individuals who were considering buying a BYD electric vehicle but had not yet done so provided the data. A partial least squares (PLS) method of structural equation modeling was used for the analysis. While green pricing and distribution had no discernible impact on purchase intent, the study's findings show that green items and green promotions have a favorable and significant impact. The significance of sustainable product and promotion tactics is emphasized by these findings.